2018
DOI: 10.3390/ijms19030646
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Central Antioxidant Property of Nuclear Factor Erythroid 2-Related Factor 2 Worsens Circulatory Homeostasis with Baroreflex Dysfunction in Heart Failure

Abstract: Heart failure is defined as a disruption of circulatory homeostasis. We have demonstrated that baroreflex dysfunction strikingly disrupts circulatory homeostasis. Moreover, previous many reports have suggested that central excess oxidative stress causes sympathoexcitation in heart failure. However, the central mechanisms of baroreflex dysfunction with oxidative stress has not been fully clarified. Our hypothesis was that the impairment of central antioxidant property would worsen circulatory homeostasis with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In addition, the HRJSDcd-E2d and HRJSDcd-LD1d indices showed that steady (E2) and low decreasing (LD1) diastolic blood pressure patterns, independent from all BBI patterns, are more frequent in CON subjects. These indices suggest a worsened circulatory homeostasis in IDC patients and support the idea of the influence of baroreflex activity in pathological conditions (Kishi, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the HRJSDcd-E2d and HRJSDcd-LD1d indices showed that steady (E2) and low decreasing (LD1) diastolic blood pressure patterns, independent from all BBI patterns, are more frequent in CON subjects. These indices suggest a worsened circulatory homeostasis in IDC patients and support the idea of the influence of baroreflex activity in pathological conditions (Kishi, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, in this study, the CTRP1 promotor was demonstrated to bind to nuclear factor erythroid 2-related factor (Nrf2) and Nrf2 could promote CTRP1 expression. Nrf2 is described as a transcription factor that binds to antioxidant response elements with antioxidative, detoxifying, and cardioprotective properties (15,16). Nrf2 has been discovered to promote mitochondrial biogenesis while limiting oxidative stress-induced inflammatory response, cardiomyocyte apoptosis, eventually contributing to MI alleviation (17,18).…”
Section: Introductionmentioning
confidence: 99%